2017
DOI: 10.1038/s41598-017-01672-w
|View full text |Cite
|
Sign up to set email alerts
|

Paternal obesity modifies the effect of an antenatal lifestyle intervention in women who are overweight or obese on newborn anthropometry

Abstract: The contribution of paternal obesity to pregnancy outcomes has been little described. Our aims were to determine whether the effect of an antenatal maternal dietary and lifestyle intervention among women who are overweight or obese on newborn adiposity, was modified by paternal obesity. We conducted a secondary analysis of a multicenter randomised trial. Pregnant women with BMI ≥25 kg/m2 received either Lifestyle Advice or Standard Care. Paternal anthropometric measures included height, weight, BMI; waist, hip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Another possible explanation is the key role that fathers have in the offspring eating habits and physical activity [32][33][34]. In the present study, many fathers of children from obese mothers had a remarkably high body weight, possibly moderating the effect of the lifestyle interventions [35]. Finally, future studies on the long-term effectiveness of lifestyle interventions during pregnancy could potentially benefit from a smaller age range when assessing the children.…”
Section: Discussion/conclusionmentioning
confidence: 67%
“…Another possible explanation is the key role that fathers have in the offspring eating habits and physical activity [32][33][34]. In the present study, many fathers of children from obese mothers had a remarkably high body weight, possibly moderating the effect of the lifestyle interventions [35]. Finally, future studies on the long-term effectiveness of lifestyle interventions during pregnancy could potentially benefit from a smaller age range when assessing the children.…”
Section: Discussion/conclusionmentioning
confidence: 67%
“…One study assessed dietary intake between 8 and 12 weeks and found carbohydrate consumption was associated with increase in birthweight, whereas fat intake was associated with lower birthweight [ 19 ]. It is also likely that the fetal programming of infant growth patterns is much more complex, with the impact of epigenetics, paternal factors, postnatal environment [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is growing interest in strategies to optimise both maternal and paternal dietary intake and weight in the peri-conceptual period [ 3 , 58 , 59 ]. This primary prevention strategy may reduce the intergenerational transmission of obesity from mother to child and may improve pregnancy outcomes [ 2 , 45 , 60 ]. Further studies are required to understand the timing of and factors relating to programming of fetal growth and body composition.…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetic changes in their offspring have been associated with father's diet. A growing epidemiologic literature shows that fathers' weight and BMI status independently influences the birth weight, obesity, and diabetes of their offspring (e.g., Dodd et al 2017). For example, during Swedish famines, low and high food availability in pre-pubescent adolescents males led to changes in their children's and grandchildren's obesity, diabetes, and cardiovascular health, especially among sons, independent of their mother's health and food exposure; these were epigenetic changes too fast for spontaneous genetic alterations (Brygren et al 2001;Kaati et al 2002).…”
Section: Paternal Epigenetic Contributionsmentioning
confidence: 99%
“…There is increasing theoretical recognition that fathers could directly contribute to infant obesity prevention and metabolic health, perhaps starting even prior to birth (Davison et al 2019), yet few nutrition interventions directly target fathers (Morgan et al 2017;Davison et al 2017). Father's own weight is an independent predictor of childhood obesity (Freeman et al 2012;Dodd et al 2017).…”
Section: Paternal Reproductive Biologic and Social Health That Could Enhance Their Partner's Reproductive Health Biologymentioning
confidence: 99%